Teratology in the twentieth century : congenital malformations in humans and how their environmental causes were established - Kalter, Harold (Elsevier, 2003)
This book is an an up-to-date survey and summary of present knowledge and future expectations regarding the environmental causes of congenital malformations in human beings, beginning with the earliest discoveries of the 20th century up to the latest ideas and problems at its end, presents views and comments on the progress made over the century in understanding human prenatal maldevelopment.